Anti-arthritic action of cardamonin in rheumatoid arthritis-induced rat model - Voon, Fui Ling (2016)
Rheumatoid arthritis (RA) is a chronic autoimmune disease which causes joint deformity. The well-being and productivity of RA patients are negatively affected as they constantly experience painfulness in their swollen joints. Current treatments for RA such as disease-modifying anti-rheumatic drugs (DMARDs), glucocorticoids, and non-steroidal anti-inflammatory drugs (NSAIDs) cause adverse effects such as bone marrow suppression, gastrointestinal upset, etc. Therefore, novel substances that possess potential anti-arthritic effect are of research interest. Cardamonin (2’,4’-dihydroxy-6’-methoxychalcone) is a naturally occurring chalcone. It is frequently found in plants of Zingiberaceae family such as ginger, a common cooking ingredient for Asians. Cardamonin was reported to suppress the secretion of tumour necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) in induced cell lines. Also, cardamonin had shown antinociceptive activity in chemical-induced mice abdominal writhing test. Thus, cardamonin was chosen to investigate its anti-arthritic effect on complete Freund’s adjuvant (CFA)-induced RA rat model of joint inflammation. Preliminary studies included acetic acid-induced abdominal writhing test, carrageenan-induced acute paw inflammation test, and repeated dose 28-day toxicity test. Anti-arthritic experiment utilised six groups (n=6) of male Sprague Dawley rats weighing 200g to 250g. RA was induced in the rats through intraplantar (i.pl.) injection of CFA at the right hind paws. On the ninth day after arthritis induction, treatments at dosages of 0.625, 1.25, 2.5, and 5.0 mg/kg were given daily for 22 days through intraperitoneal (i.p.) injection. The positive control group was treated with dexamethasone (3.0mg/kg, i.p.) while the negative control group was given only vehicle (10.0ml/kg, i.pl.). CFA-induced inflammatory response was evaluated via volume of paw oedema using plethysmometer, while pain response was evaluated via mechanical allodynia using von Frey anesthesiometer as well as thermal hyperalgesia using plantar test instrument. Evaluation of paw volume, mechanical allodynia, and thermal hyperalgesic responses were done at three-day intervals throughout the experiment. Blood samples were collected at the end of the experiment to investigate the blood components and systemic cytokines of cardamonin-treated rats. Right hind paws of the rats were harvested for histological examination. Cardamonin significantly inhibited acetic acid-induced abdominal writhing in experimental animals. Also, cardamonin significantly reduced the acute paw inflammation in carrageenan-induced acute paw inflammation test. Repeated dose 28-day toxicity test showed that 5.0mg/kg of cardamonin did not cause toxicity effect in rats. In anti-arthritic study, plethysmometry, von Frey anesthesiometry, and plantar test measurement showed that cardamonin resulted in significant inhibition on CFA-induced inflammatory and pain responses at the doses of 0.625, 1.25, 2.5, and 5.0 mg/kg (i.p.). The complete blood count showed that cardamonin caused significant effect on the blood components of CFA-induced rats. Enzyme-linked immunosorbent assay (ELISA) demonstrated that there was significant inhibition in TNF-, IL-1, and IL-6 in cardamonin-treated RA rats. Besides, histological study showed that cardamonin has the potential to suppress the growth of pannus invasion in the joint cavity. The present study revealed that 0.625, 1.25, 2.5, and 5.0 mg/kg of cardamonin caused significant inhibition on CFA-induced RA rats.